Language Choice in social media Instagram Found In @Jokowi Account - Utami, Etika Widi; Rokhman, Fathur; Mardikantoro, Hari Bakti (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research explains the language choices, characteristics, and influential factors on Instagram found in @Jokowi's account. The researcher collected the data by reading and listening with a recording technique. The advanced data collection technique free-participant observation in a speech, recording and noting techniques. The researcher used the coding method to analyze the data. The findings showed the language choices were a singular variety of Indonesian language, singular variety of English, Indonesia-Javanese code-switching, Indonesia-English code-switching, word-code mixing, and phrase-code mixing. The characteristics of the language were formal and non-formal language. The non-formal language covered slank, expression, abbreviation, specific term, foreign term, vernacular language. The researcher also found formal language uses. The most influential factors of the language were the objectives of the utterance, the topic of the utterance, the speech participants, and the intention-goal factor.